IMPROVING SOCIAL COMMUNICATION SKILLS IN AUTISM SPECTRUM DISORDERS USING PROGRAMMABLE TOY ROBOTS - Marzano, Gilberto; Zorzi, Simone; Tambato, Valeria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Autism spectrum disorders (ASD) are a group of lifelong disabilities that affect people’s ability to communicate and understand social cues. An individual with ASD has difficulties in recognizing body language, making eye contact, and understanding other people’s emotions. Rapid progress in technology offers increasing possibilities for innovation in treatment for individuals with ASD.In recent years, advances have enabled programmable toy robots (PTRs) to help individuals improve their social skills and communication abilities. Over the past decade, the use of PTRs with autistic children has received considerable attention, even though research on this topic is in its infancy.This article analyzes the recent progress in the use of PTRs in the ASD scope. It illustrates an exploratory research conducted on four adolescents with ASD aimed at defining an experiment to evaluate the effectiveness of PTRs in their social communication.The exploratory research results are encouraging, although they demonstrated the complexity in determining the feasibility and validity of robots in the social communication of autistic people.